Radiosonde raw data measured during POLARSTERN cruise PS130/1, links to files - Holger Schmithüsen; Frank Otte; Antje Elsäßer; Julia Wenzel (PANGAEA, 2025)
The meteorological observatory Polarstern continuously performs radiosoundings during times of ship operation. Typically, there is one launch to full altitude at 12 UTC every day. Additionally, there often is a launch with a smaller balloon for forecasting purposes (helicopter operations) around 6 UTC. All data published here is left "as recorded", no quality control was applied.